(untitled) (International Journal of Engineering and Computer Science, 2017)
A "smart grid" is a reading meter which includes a various application and unit measures including reading meters. Smart meter collect the daily time information. Smart meter collect daily data and that data is encrypted. The main aim of this paper is to compare the existing systems with LAC scheme an various concepts used in LAC of secure communication data exchange. This survey paper presents the different techniques which is used in LAC of secure communication data exchange